The Use of Elements of Computational Intelligence in Problems of Forecasting of Corroding Constructions Durability - Korotka, L.I.; Korotka, Y.A. (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2017)
The modeling is considered of behavior of metal structures with changing geometric characteristics, which functioning in aggressive external environments. Information about the parameters of the external environment is incomplete or inaccurate. To formalize this information proposed to use the mathematical apparatus of the theory of fuzzy sets and interval analysis. The opportunities of the application of the ways have been examined.